2020
DOI: 10.2217/fvl-2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

Perversely Expressed Long Noncoding Rnas Can Alter Host Response and Viral Proliferation in SARS-CoV-2 Infection

Abstract: Background: Regulatory roles of long noncoding RNAs (lncRNAs) during viral infection has become more evident in last decade, but are yet to be explored for SARS-CoV-2. Materials & methods: We analyzed RNA-seq dataset of SARS-CoV-2 infected lung epithelial cells to identify differentially expressed genes. Results: Our analyses uncover 21 differentially expressed lncRNAs broadly involved in cell survival and regulation of gene expression. These lncRNAs can directly interact with six differentially expressed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 147 publications
0
45
2
Order By: Relevance
“…Regulation of catabolism of nucleic acids and their metabolites can contribute to viral pathogenesis [ 28 ]. For instance, SARS-CoV-2 nsp8 appears to reduce the catabolism capacity of the host exosome complex against viral mRNAs [ 29 ]. In addition, components of exosome complex (EXOSC2, EXOSC3, EXOSC5, and EXOSC8) included in the set of SARS-CoV-2-associated host proteins presented highlighted function involving nucleic acid catabolism processes (supplementary table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of catabolism of nucleic acids and their metabolites can contribute to viral pathogenesis [ 28 ]. For instance, SARS-CoV-2 nsp8 appears to reduce the catabolism capacity of the host exosome complex against viral mRNAs [ 29 ]. In addition, components of exosome complex (EXOSC2, EXOSC3, EXOSC5, and EXOSC8) included in the set of SARS-CoV-2-associated host proteins presented highlighted function involving nucleic acid catabolism processes (supplementary table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to mucoinflammatory factor encoding mRNAs, another type of RNA, lncRNAs, have now been found to play vital roles in regulating the innate immune responses (12,13) and recent studies have shown that specific lncRNAs are differentially expressed during hostpathogen interactions following viral infection (18,19,34,35). That said, our group identified two novel epithelial lncRNAs, LASI (lncRNA on antisense strand to ICAM-1) and TOSL (TNFAIP3opposite strand lncRNA) that are differentially expressed during the mucus hypersecretory response (36) and blocking these lncRNA expression alleviates the mucin hyperexpression.…”
Section: Sars-cov-2 Infected Airway Tissue Model Show Increased Expression Of Immunomodulatory Lncrnasmentioning
confidence: 99%
“… 340 ), which was previously shown to promote inflammatory injury in lung tissue via negative regulation of IL-8 (ref. 343 ), and of MIR3142HG 344 , 345 , which is also induced by pro-inflammatory IL-1β and positively regulates secretion of IL-8 and CCL2 (neutrophil/monocyte chemoattractant) in lung fibroblasts 346 . The complex interactions between host and viral noncoding genes in SARS-CoV-2 infection is thus only starting to be explored, but the findings so far hint at diverse opportunities to target COVID-19 disease with RNA-based therapeutics.…”
Section: Introductionmentioning
confidence: 99%